Effectiveness of lyophilized amniotic membrane as barrier in guided bone regeneration in rabbit tibias (2014)
This study aimed to determine the effect of lyophilized amniotic membrane used as a biological barrier in the process of guided bone regeneration in rabbit tibias. Materials and Methods: Were used 10 New Zealand white rabbits of 2 to 2.5 Kg and 4-6 months of age; in which circular bone defects of 4mm in diameter were created in the lower region of the rabbit hind limb (tibias). 2 groups were formed: a control group (no membranewas placed) and the experimental group (lyophilized amniotic membrane was placed as a barrier). The animals were sacrificed at 6 weeks after surgery, performing a clinical, radiological and histological analysis of the area where the bone defects were created. Results: Clinically was found an absence of inflammatory reaction (100%) and absence of infectious processes (100%), in the histological examination, 87.5% of the samples of the study group showed the presence of mature compact bone while in the group control reported a 100% absence. Conclusion: We concluded that bone regenerationwas significantly higher in the defects covered with lyophilized amniotic membrane compared with the samples from the control group.